Who counts as Filipino? Philosophical issues of identity and the Chinese Filipino - Dela Cruz, Noelle Leslie (Budhi: a Journal of Ideas and Culture, 2015)
This article examines some recent philosophical attempts to make sense of “identity” in light of the intersecting categories of race, ethnicity, and culture. It addresses a perennial issue brought up recently with regard to Filipino Chinese: Who counts as “Filipino?” Behind this question are assumptions that I scrutinize philosophically: that there is a “Filipino” and it is possible to identify who counts as such and who does not. I begin with a survey of existing paradigms of identity which I then apply to a critical analysis of recent public discourse spawned by anti-Chinese statements made by a prominent Filipino novelist. I conclude with ethical prescriptions for conceptualizing Filipino identity in light of the complex fissures revealed by the aforementioned issue.